Evaluation of Pb doped Poly(lactic acid) (PLA)/Poly(ethylene glycol) (PEG) blend composites regarding physicochemical and radiation shielding properties - Yilmaz, Mucahit; Pekdemir, Mustafa Ersin; Oner, Ecem Ozen (Pergamon-Elsevier Science Ltd, 2023)
In this study, composites of lead element, which is used to eliminate the harmful effects of radiation, were prepared with a polymer blend with shape memory properties. Poly(lactic acid) (PLA)/Poly(ethylene glycol) (PEG) blend films doped with different amounts of lead were obtained by solvent casting method. Polymer blend/Pb composites were characterized by Attenuated total reflectance infrared spectroscopy (ATR-IR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscope (SEM). When the thermal analysis results were examined, it was observed that the thermal stability of the polymer blend decreased as the Pb percentage increased. It was concluded that the shape memory properties were the best in the polymer blend containing 4% Pb. X-ray diffraction (XRD) results showed that the 2 circle minus peaks at 31.2 degrees, 36.3 degrees, 52.3 degrees, 62.1 degrees and 65.2 degrees represent Pb with a characteristic cubic shape. It was calculated from XRD that the polymer blend composite containing 16% Pb had the highest degree of crystallinity with 31.41%. Finally, in the study, the gamma irradiation of the obtained polymer blend/Pb composites were examined. It was seen that the linear absorption capacity increased with increasing Pb percentage, which can be interpreted as an increase in the shielding ability.
Keywords: Poly(lactic acid) (PLA); Composite; Poly(ethylene glycol) (PEG); Gamma irradiation; Lead